A Study of the Mystical Prose of addressing in the Book of Al-ensan Al-Kamel by AzizoddinNasafi - Ghodratollah Khayatian; Elham Rezvani Moghaddam (مطالعات زبانی و بلاغی)
Meaning and rhetorical science have been very effective in shaping mystical language؛ the way mystics have been able to convey their inexpressible mystical experiences and teachings through these rules and principles. It is undoubtedly a prerequisite for the influence of the sciences of meaning and rhetoric on the author's Understand the mood of the audience correctly. AzizoddinNasafi has tried to address the mystical prose in the book Al-ensan al-Kamel, in the minds and souls of their audiences, to convey to them their various goals and purposes. This book, like his other works, is influenced by his mysticism and mysticism, and also teaches mystical experiences while being educated. A relative knows very well that the impact of speech is far greater than writing ؛ Because speech is the result of direct communication between the speaker and the listener; it therefore uses the speech to create a close and dynamic connection with the audience and to keep it satisfied ؛ So that the audience understands both the mystical teaching concepts and the active and constant presence in the text. This research uses a descriptive-analytical approach to investigate the types of addressing in the mystical prose of relational addressing. The result of this study shows that Nasafi has attempted to use a variety of secondary meanings instead of dealing with the crude concepts of news sentences. In this way to increase the impact of his words in relation to the audience and to help seekers of the path in various ways along this path.